The financier : the critical edition - Dreiser, Theodore, 1871-1945 (Dreiser, Theodore, 1871-1945. Works. 1988., 2010)
Aricher, considerably more complex version of The Financier by Theodore Dreiser, whose critique of American business practices led reviewers to laud him as the equal of the great European realists. Roark Mulligan's commentary offers a cogent, thorough, and eminently readable exploration of late-nineteenth-century American business practices."-Keith Newlin Editor Of A Theodore Dreiser Encyclopedia.